Strategi Pengelolaan Pantai Parangtritis Sebagai Daya Tarik Wisata Alam Di Kabupaten Bantul Pada Era New Normal - Fajar Subeni; Achmad Andi Rif'an (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2022)
The Covid-19 pandemic has an impact not only on health but also the economic sector and tourism sector in the world. The New Normal Era is an action or behavior carried out by the community to implement a new lifestyle that is different from the previous one which was applied in all sectors, especially tourism. The purpose of this study is to formulate a management strategy for Parangtritis Beach during the new habit and analyze the internal and external environment as a basis for consideration and evaluation for Parangtritis Beach managers. TThe results of this study are in the form of strategies that must be carried out by managers and related agencies in the management of Parangtritis Beach: optimizing the promotion of Parangtritis Beach for the New Customs Period, maintaining the stability of the number of tourists by considering health protocols, making events by complying with and considering health protocols, namely providing health posts, limiting the number of visitors, conducting routine monitoring, wearing masks, maintaining distance, washing hands with soap, using hand sanitizer, bathing after traveling, cleaning goods with disinfectant liquid, making appeals to the community, of course as members of tourism to fulfill health protocols to prevent the spread of covid-19.Keywords: Covid-19 Pandemic; Parangtritis Beach; New Normal Era; Management Strategy